Eficiência agronômica e persistência de herbicidas pré-emergentes na cultura da soja - Patel, Felipe (2018)
The occurrence of cases of resistance of weeds to the glyphosate herbicide, has made it necessary to adopt new practices integrated in weed management. The use of herbicides with residual effect in soil combined with soil cover with straw is essential for reducing selection pressure and reducing the number of glyphosate applications. The present work evaluated the efficiency and environmental performance of the chlorimuron-ethyl, diclosulam, flumioxazin and saflufenacil herbicides applied to soils of the Southwest of Paraná classified as a Reddish Nitrous Oxisol in two systems, with black oat straw and without straw on the surface of the ground. Two field experiments (Pato Branco-PR and Dois Vizinho-PR) and three bioassays were carried out under greenhouse conditions. Field experiments were carried out with soybean cultivar BMX Elite IPRO using a randomized complete block design with sub-divided plots in a 4 x 2 x 5 scheme. The herbicides (chlorimuronethyl) were allocated to the main plots, diclosulam, flumioxazin and diclosulam), the treatments with and without black oat straw on the soil surface and on the subsubplots were the herbicide concentrations (0X, 0.3X, 0.6X, 1X and 2X). The first bioassay made the selection of cultivated species for use in subsequent bioassays. The second bioassay consisted of the calibration of doses to determine the response of the species chosen for each herbicide. The third bioassay determined the persistence of the herbicides studied in the soil, from soil samples collected in the Pato Branco field experiment. In the field experiments, weed density, visual weed control, soybean toxicity, and yield and soybean yield components were evaluated. In the bioassays were evaluated plant height, phytotoxicity, green plant mass and dry matter. The herbicides chlorimuron-ethyl, diclosulam, flumioxazin and saflufenacil at the doses tested showed low phytotoxicity and weed control similar among herbicides. The presence of black oat straw on the soil surface acted synergistically with herbicides tested in weed control. The use of bioindicator plants was efficient to detect the presence of herbicides in the soil and the degree of sensitivity of the tested species varied according to the species tested, being the cucumber selected for the bioassay for bioavailability and persistence of the herbicides chlorimuron-ethyl, diclosulam, flumioxazin and saflufenacil in soil. The increasing order of persistence of the herbicides in the soil on the mean of straw with and without straw was saflufenacil <flumioxazin <chlorimuron-ethyl <diclosulam.